Pengaruh Reward Dan Punishment Terhadap Motivasi Kerja Pegawai Di Kantor Kecamatan Tidore Selatan Kota Tidore Kepulauan - Hafsa Yusuf; Abdul Kadir Ali; Yusuf Kamis (Jurnal Ilmiah Wahana Pendidikan, 2023)
Giving reward and punishment is an important factor that is applied to support employee motivation and provide sanctions for those who lack discipline at work. Both can affect employee motivation, and the aim is to increase work motivation so that employee performance can be maximized. The purpose of this study was to determine the effect of reward and punishment partially and simultaneously on the work motivation of employees in the South Tidore District Office, Tidore Islands City. This study uses quantitative data types obtained from the results of a questionnaire with a five-point Likert scale. The research sample consisted of 70 employees in South Tidore District. The data analysis method used is Multiple Linear Regression Analysis using the Statistical Package for Social Science (SPSS) Software. The results showed that the reward variable partially had a significant effect on employee motivation with a significant value of 0.043 ≤ 0.05, while the punishment variable had no significant effect on employee motivation with a significant value of 0.354 ≥ 0.05. However, reward and punishment simultaneously have no effect on employee motivation at the South Tidore District Office, this can be seen from the results of the calculation of the F test with a significant value of 0.063 ≥ 0.05.